Interpreting Meditation as an Interreligious Occasion: an Interrituality Approach - Aditya, Refan (Panangkaran: Jurnal Penelitian Agama dan Masyarakat, 2024)
This research examines meditation as a form of interreligious engagement through an interrituality approach. The concept of interrituality involves interreligious encounters that are catalysed by rituals. The meditation considered here is a public meditation organised by one of the Buddhist institutions in Indonesia, namely Karangdjati vihara Yogyakarta. This research uses semi-structured interviews and participatory observation of regular non-Buddhist participants in the vihara. Drawing on the interrituality approach, this research aims to present the plurality of interpretations of the one Buddhist ritual of meditation based on the participants' immersions, and needs that allows for the sharing of religious experiences in a hospitality moment. In that way, this study aims to contribute to broadening the interest of interreligious studies from theological, theoretical, and discursive dialogue to the more practical, lived interreligious encounters through the realm of ritual. [Penelitian ini meneroka meditasi sebagai momen perjumpaan lintas agama melalui pendekatan interrituality. Konsep interrituality bermakna perjumpaan lintas agama yang diwujudkan oleh ritual. Meditasi yang diteliti adalah meditasi umum yang diselenggarakan salah satu institusi agama Buddha di Indonesia, yaitu vihara Karangdjati Yogyakarta. Penelitian ini menggunakan metode wawancara semi-struktur dan observasi partisipatif terhadap partisipan reguler non-Buddhist di vihara. Dengan menggunakan pendekatan interritualitas, penelitian ini berupaya menampilkan pluralitas penafsiran atas satu ritual meditasi berdasarkan penghayatan dan kebutuhan para partisipannya yang memungkinkan terjadinya saling berbagi pengalaman religius dalam suasana ramah tamah. Dengan cara itu, penelitian ini hendak berkontribusi untuk memperluas perhatian studi lintas agama dari dialog teologis, teoritis dan diskursif ke perjumpaan lintas agama yang lebih praktis dan hidup melalui ranah ritual.]